Lubricity assessment of ultra-low sulfur diesel fuel (ULSD), biodiesel, and their blends, in conjunction with pure hydrocarbons and biodiesel based compounds. (February 2022) - Tat, Mustafa Ertunc; Çelik, Osman Nuri; Er, Umit; Gasan, Hakan; Ulutan, Mustafa
This research aimed to investigate the lubricity and wear properties of ultra-low sulfur diesel fuel (ULSD) blended with biodiesel and doped with biodiesel-based organic compounds. In this work, neat n -dodecane served as a surrogate for ultra-low sulfur diesel fuel (ULSD), Fischer Tropsch, and renewable diesel fuels. Additionally, some pure hydrocarbons were also investigated for unsaturation and carbon chain length. Tribological characterization was conducted on quenched and tempered AISI 4140 steel, substituting diesel fuel pump material, and using the ball-on-disc technique. The wear rates of biodiesel samples were about 2–4 times less than the vegetable oils. Esterification improves the lubricity of vegetable oils. The wear rate of biodiesel is about 5–7 times greater than that of fossil base commercial Eurodiesel fuel. Using biodiesel as an additive had a significant effect on the lubricity of pure n -dodecane, adding 2 wt% biodiesel resulted in 5–7 times wear rate reduction that equivalent to the lubricity level of commercial Eurodiesel fuel. Wear rates of pure hydrocarbons showed that wear is reduced with increasing chain length and unsaturation.